Security in islamic finance shariah compliance and the new civil court's approach to dispute resolution - Mohamad, Ani Munirah; Md Nor, Mohd Zakhiri; Rachmawati, Irma (Magister Kenotariatan Universitas Pasundan, 2023)
Malaysia has a dual financial system that includes both conventional banking and Islamic banking. Over time, Islamic banking has evolved to the point where it has enticed traditional banks to offer Shariah-compliant products as well. However, even though conventional banks have provided Shariah-compliant products, the Islamic bank's obligation to provide Islamic banking services remains. The goal of this article is to look at the measures in the Islamic Financial Services Act 2013 that assure Shariah-compliance security for Islamic banks. This paper also investigates the current approach of civil courts in resolving disputes. The qualitative research methodology was used in this paper. The phenomenology method was used in the research design. Data will be gathered from journals, statutes, and case law. The data will be analyzed using the content analysis method. This paper concludes that it is a heavy-duty of every Islamic bank to ensure Shariah compliance security, and the current civil court approach is that the Islamic banking agreement is still enforceable even if it does not comply with Shariah law. Islamic banking agreements that are in accordance with Shariah law or are not perfectly in accordance with Shariah law are both valid and legal